Hematophagous ectoparasites affect nestling size and physiology, but not apparent survival - Emma N. Stierhoff; Julianna M. Carpenetti; Sarah A. Knutie; Jon W. Wallace; Michael W. Butler (Journal of Ornithology, 2024)

Wildfire and Family Forest Owners: Concern, Advice, and Wildfire Reduction Behaviors from the United States National Woodland Owner Survey - Sarah M Butler; Brett J Butler; Emma M Sass (Forest Science, 2024)
Extreme wildfire is an increasing threat to lives, property, and ecosystems across the United States and many parts of the world. Family forest owners (FFOs) own a large percentage of forestland in the United States, and actions and behaviors on their forestland have a large impact on wildfire prevention and mitigation across the landscape. Using data from the USDA Forest Service’s 2018 National Woodland Owner Survey, we investigated national and regional FFO wildfire attitudes and behaviors. We see that concern for wildfire is relatively high across the United States; however, this concern does not always lead to wildfire reduction activities on the landscape. There is some variation among regions, with concern about wildfire and past wildfire reduction activities highest in the western US (76% and 37%, respectively), followed by the South (63% and 11%, respectively), and lowest in the northern region (50% and 8%, respectively). Understanding these aspects of wildfire and FFOs on a national level provides a broader context for the more focused studies across the country and acts as a launch point for more in-depth research in the future. Study Implications: This study assesses family forest owner (FFO) wildfire concern, information needs, and action, both past and intended, at national and regional levels across the United States. As wildfire is predicted to increase in frequency and severity into the future due to climate change, this research provides a reference line and a launch point for future studies. Understanding current concern levels and landowner characteristics can inform programs and policies aimed at mitigating severe wildfires. For example, the disconnect between concerns and actions can be used as an entry point for motivating additional owners to take steps towards active management. Concentrating efforts in fire-prone areas is important, but seeing that wildfire is a concern of family forest owners across much of the country suggests that this can be an important issue for starting conversations with many owners and possibly increasing their engagement with conservation efforts.

Trends in United States Family Forest Owners’ Attitudes, Behaviors, and General Characteristics from 2006 to 2018 - Emma M Sass; Brett J Butler; Jesse Caputo; Emily S Huff (Forest Science, 2023)
Family forest owners (FFOs) control a plurality of forestland in the United States, and the decisions these landowners make have a profound impact on the landscape. Most research on FFOs consists of cross-sectional studies, although many of these recognize the importance of capturing long-term trends to understand whether and how FFO attitudes, behaviors, and general characteristics are changing. We use data from the 2006, 2013, and 2018 iterations of the USDA Forest Service, National Woodland Owner Survey (NWOS), with a bootstrapping approach to identify significant changes across these time periods among FFOs with 4+ hectares of forestland. Total FFO hectares decreased and FFO ownerships trended downward over the study period. A decreasing proportion of FFOs owned farms or homes near their forestland, harvested timber, or received advice. Demographic shifts include an increase in age and education level from 2006 to 2018, and an increase in FFOs of color from 2006 to 2013. Overall, we find a trend towards decreased traditional engagement and management and a slight increase in owning land for its amenity values. Understanding temporal trends in FFO characteristics, attitudes, and behaviors will help policymakers and forestry professionals inform and update their outreach, technical support, and financial assistance programs. Study Implications: Families and individuals hold more forestland than any other ownership group in the United States. We use nationwide survey data from 2006, 2013, and 2018 to determine whether and how these landowners are changing over time. The total forestland held by FFOs decreased between 2006 and 2018, and there has been a decrease in traditional forest management and engagement, such as through timber harvesting and nearby farm ownership. This study provides insights for policies, programs, and outreach and a foundation for future long-term comparisons of this group.

Wood Supply from Family Forests of the United States: Biophysical, Social, and Economic Factors - Brett J Butler; Emma M Sass (Forest Science, 2023)
Wood products are an essential provisioning ecosystem service with US forests providing nearly one-fifth of global wood supply. As of 2018, an estimated 46% of the annual wood harvested came from corporate forests, 42% came from family forests, and the remainder came from other private, public, and Tribal forests. The supply of wood from corporate forests is well described by traditional economic models, but the supply from family forests is much less well understood. This article combines data from three components of the USDA Forest Service’s Forest Inventory and Analysis program—plots, landowner surveys, and mill surveys—with other data to model the wood supply from family forests in the United States. Results are summarized in terms of bivariate relationships and a logistic regression model. The model results show that basal area, stand origin, forest type, having timber as an ownership objective, the amount of annual income derived from their forestland, proximity to a mill, management advice, and region are significantly associated with family forest timber harvesting. The results should be useful for forest industry analysts and others interested in understanding the current and potential future supply of wood from family forests. Study Implications: Family forests provide an estimated 42% of the annual timber harvested in the United States. It is important to understand the factors affecting their harvesting behaviors to design effective policies and programs to ensure a continual supply and sustainable management of this critical resource. This article shows that timber harvesting by family forest owners is influenced by a combination of biophysical, social, and economic factors, including basal area, stand origin, forest type, having timber as an ownership objective, the amount of annual income derived from their forestland, proximity to a mill, management advice, and region. These results suggest that programs aimed at increasing the area covered by planted stands, the area covered by softwood stands, and the number of owners receiving forest management advice may be particularly influential in maintaining and increasing the amount of wood harvested from family forests.

Biofilm-Mediated Fragmentation and Degradation of Microcrystalline Cellulose by Cellulomonas flavigena KU (ATCC 53703) - Emma S. Young; John D. Butler; Sara J. Molesworth-Kenyon; William J. Kenyon (Current Microbiology, 2023)

The impact of long-term land leases on farm investment: Evidence from the Irish dairy sector - Tracy Bradfield; Robert Butler; Emma J. Dillon; Thia Hennessy; Jason Loughrey (Land Use Policy, 2023)

Attachment to land and its downfalls: Can policy encourage land mobility? - Tracy Bradfield; Robert Butler; Emma J. Dillon; Thia Hennessy; Jason Loughrey (Journal of Rural Studies, 2023)

United States Family Forest Owners’ Awareness of and Participation in Carbon Sequestration Programs: Initial Findings from the USDA Forest Service National Woodland Owner Survey - Emma M Sass; Jesse Caputo; Brett J Butler (Forest Science, 2022)
Family forest owners (FFOs) hold a plurality of forestland in the United States, and programs and markets exist that compensate landowners for sequestering and storing increased carbon through extended rotations, improved forest management, and increased forest cover. We used USDA Forest Service National Woodland Owner Survey (NWOS) data from 2018 to estimate the number of ownerships and their associated acreage that are enrolled, that are familiar but not enrolled, and that are unfamiliar with these programs, as well as differences in attributes among these groups. As of 2018, less than 0.1% (SE < 0.1%) of FFOs are enrolled in carbon sequestration programs, and collectively they hold an estimated 400,000 ha (SE = 100,000). FFOs who are enrolled have larger holdings, are more likely to participate in other programs, and are more concerned about climate change, among other characteristics. Most FFO holdings are too small to be viable in traditional carbon programs, although new and evolving programs might enable smaller landholdings to be feasible to enroll. Knowing the characteristics of ownerships that are enrolled or aware of programs will allow for more informed design and implementation; future monitoring will be important to identify trends as these programs become more widespread.

Functional traits driving species role in the structure of terrestrial vertebrate scavenger networks - Esther Sebastián‐González; Zebensui Morales‐Reyes; Francisco Botella; Lara Naves‐Alegre; Juan M. Pérez‐García; Patricia Mateo‐Tomás; Pedro P. Olea; Marcos Moleón; Jomar Magalhães Barbosa; Fernando Hiraldo; Eneko Arrondo; José A. Donázar; et al. (Ecology, 2021)
Species assemblages often have a non‐random nested organization, which in vertebrate scavenger (carrion‐consuming) assemblages is thought to be driven by facilitation in competitive environments. However, not all scavenger species play the same role in maintaining assemblage structure, as some species are obligate scavengers (i.e., vultures) and others are facultative, scavenging opportunistically. We used a database with 177 vertebrate scavenger species from 53 assemblages in 22 countries across five continents to identify which functional traits of scavenger species are key to maintaining the scavenging network structure. We used network analyses to relate ten traits hypothesized to affect assemblage structure with the “role” of each species in the scavenging assemblage in which it appeared. We characterized the role of a species in terms of both the proportion of monitored carcasses on which that species scavenged, or scavenging breadth (i.e., the species “normalized degree”), and the role of that species in the nested structure of the assemblage (i.e., the species “paired nested degree”), therefore identifying possible facilitative interactions among species. We found that species with high olfactory acuity, social foragers, and obligate scavengers had the widest scavenging breadth. We also found that social foragers had a large paired nested degree in scavenger assemblages, probably because their presence is easier to detect by other species to signal carcass occurrence. Our study highlights differences in the functional roles of scavenger species and can be used to identify key species for targeted conservation to maintain the ecological function of scavenger assemblages.

Dynamics of Large Corporate Forestland Ownerships in the United States - Emma M Sass; Marla Markowski-Lindsay; Brett J Butler; Jesse Caputo; Andrew Hartsell; Emily Huff; Amanda Robillard (Journal of Forestry, 2021)
Ownership of forestland in the United States has changed in recent decades, including the proliferation of timber investment management organizations (TIMOs) and real estate investment trusts (REITs), with the potential to alter forest management and timber supply. This article quantifies forest ownership transitions among ownership categories between 2007 and 2017 and investigates how and why large corporate ownerships own and manage their forestlands. Ownership transitions were determined from refined USDA Forest Service, Forest Inventory and Analysis data; we also conducted a survey of large corporate forestland ownerships. Corporate forestland acreage increased between 2007 and 2017, while family and public forestland decreased. Large corporate landowners report multidimensional, financially focused land management, although industry, timber investment management organizations, real estate investment trusts, and other owners report some different motivations and income streams. This work provides a baseline to track future ownership transitions and the behaviors of large corporate forestland owners.

One Size Does Not Fit All: Relationships between Size of Family Forest Holdings and Owner Attitudes and Behaviors - Brett J Butler; Jesse Caputo; Amanda L Robillard; Emma M Sass; Chris Sutherland (Journal of Forestry, 2021)
An estimated 10 million families, individuals, trusts, and estates own 39 percent of the forestland in the United States, excluding interior Alaska. Using segmented regression, the relationships between size of forest holdings and the attitudes and behaviors of these family forest ownerships were tested using data from the 2018 iteration of the USDA Forest Service’s National Woodland Owner Survey. All 16 variables tested have significant relationships with size of forest holdings, and 13 have one or more breakpoints, ranging from 40 to 5,854 ac, where the relationships between the variables change. Timber as a reason for owning, timber harvesting activities, management plan, advice received, land certified, tax program participation, cost share, recreation, land tenure, recreation, taxes and heirs as concerns, land transfer, and income from forestland have positive relationships with size of forest holdings; resident ownership has a negative relationship; and wildlife as a reason for owning and owner age have mixed relationships.

The effects of cannabinoid 1 receptor compounds on memory: a meta-analysis and systematic review across species - Faith Borgan; Katherine Beck; Emma Butler; Robert McCutcheon; Mattia Veronese; Anthony Vernon; Oliver D. Howes (Psychopharmacology, 2019)

Sublethal effects of natural parasitism act through maternal, but not paternal, reproductive success in a wild population - Olivia Hicks; Jonathan A. Green; Francis Daunt; Emma J. A. Cunningham; Mark Newell; Adam Butler; Sarah J. Burthe (Ecology, 2019)
Parasites are a major component of all animal populations. Males and females often differ in their levels of parasite prevalence, potentially leading to sex differences in the impact of parasitism on fitness, with important implications for the evolution of parasite and host traits including resistance, tolerance, and virulence. However, quantitative measures of the impact of parasitism under free‐living conditions are extremely rare, as they require detailed host demographic data with measures of parasite burden over time. Here, we use endoscopy for direct quantification of natural‐parasite burdens and relate these to reproductive success over 7 yr in a wild population of seabirds. Contrary to predictions, only female burdens were associated with negative impacts of parasitism on breeding success, despite males having significantly higher burdens. Female reproductive success declined by 30% across the range of natural parasite burdens. These effects persisted when accounting for interannual population differences in breeding success. Our results provide quantitative estimates of profound sub‐lethal effects of parasitism on the population. Importantly, they highlight how parasites act unpredictably to shape ecological and evolutionary processes in different components of the same population, with implications for demography and selection on host and parasite traits.

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Applications of pedigree-based genome mapping in wheat and barley breeding programs - Mandy Christopher; Emma Mace; David Jordan; David Rodgers; Paul McGowan; Ian Delacy; Phillip Banks; John Sheppard; David Butler; David Poulsen (Euphytica, 2007)